Fabric nomenclature comparison of fabric names used between selected fabric sellers and fashion students - Quiñola, Kim Agatha J.
ABSTRACT Fashion student customers often encounter challenges in communicating with the fabric sellers about their desired fabrics. This study aimed to compare the fabric names used by selected sellers and fashion students. Specifically, the study aimed to determine which fabrics were given the same names by the sellers and students and were named differently and accurately by the sellers and students respectively, and to investigate the roots of the strengths and limitations of both group of respondents in naming the fabrics. The research design was descriptive and qualitative. The study was limited to six market-based fabric stores, where the managers were able to accommodate. There were 176 fabrics collected. The fabric swatches were presented to purposively selected 40 students from different schools, who had already taken their courses in textiles. They were given a fabric identification test. The fabric sellers were also interviewed, and an online survey was conducted among the fashion students to determine how they learn fabric names. The fabric names collected from the respondents were categorized by the researcher into general, specific, trade and informal names. The study revealed that 53% of the 176 fabrics were named the same by both sides. They also shared the same general and informal names. The sellers were more knowledgeable of trade names due to experience and the suppliers' swatch catalogs. The students were more skilled in recognizing fiber content, imitations and specific surface characteristics because of their technical lessons on textiles and skills in critical thinking. Further studies on more types of fabrics and other fabric markets are recommended.